Neuroprotective properties of Centella asiatica (L.) urban on chronic unpredictable mild stress induced male wistar rats - Jagadeesan, Saravanan (2020)
Stress could have a major impact on the physiology and psychology of an individual. Stress can be viewed from the perspective of duration as acute and chronic. The chronic stress has a major role in the aetiopathogenesis of several neuropsychiatric conditions primarily depression. The characteristic hyper-responsiveness of glucocorticoids in these situations have an influence on the ultrastructural and biochemical functions of the neurons of the hippocampus and prefrontal cortex. The presently available medications for the management of depression have multiple limitations. They generally have long latency for positive results, are not universally suitable and have multiple adverse effects. These factors encourage the need for innovative pharmaceuticals which could override these deficiencies. The most promising source for such novel molecules are the herbs used in traditional medicines. Centella asiatica (CA) has historically prominent use in traditional medicine for its putative neuroprotective and neuro-regenerative properties. Extracts of CA were assessed in chronic stress induced rats and the results analysed. Healthy male Wistar rats of age between 8 – 10 weeks were procured and maintained under laboratory conditions. The rats were held in six groups. One group was a control. Chronic unpredictable mild stress was administered to the rest of the groups. The mild stress was delivered by restrainers, forced swimming in cold water, an overnight food and water deprivation, placement on wet bedding, placement in cage tilt, tail pinching, overcrowding the cages and changing the cage mates. These unpredictable stress were randomly delivered over 64 days. One of the group subjected to these stresses was retained as model group. The rest of the groups were administered with crude extracts of CA at the doses of 200 mg/kg, 400 mg/kg, 800 mg/kg, while one group received fluoxetine (Flx) 10 mg/kg body weight. The aforementioned medications were administered daily for 64 days, 30 minutes before the commencement of experiment. Following the sixty-four days of experiment, behavioural test including Forced Swim Test (FST), Open Field Test (OFT), Elevated Plus Maze Test (EPM) And T-Maze Test were performed. At the completion of these behavioural test, the rats were euthanised and the brain tissue were collected and blood samples obtained. The neural tissue were analysed using Nissl’s stain and transmission electron microscope (TEM). The neural tissues were also quantitatively assessed for malondialdehyde (MDA), superoxide dismutase (SOD), catalase (CAT) and acetylcholinesterase (AChE). Polymerase chain reaction (PCR) was done to identify the genes for mSOD and mCAT. The blood samples were assessed for quantitative estimation of cortisol levels. The rats which received CA extract were compared with the stress model group of rats. The rats receiving CA showed less impact on behaviour, while the Nissl’s staining revealed a higher number and density of viable neurons of hippocampus. The rats which received CA extract at dosages of 400 and 800 mg/kg had significantly less ultrastructural alterations in the mitochondria, nucleus, synapse and myelin sheath. In the same rat groups, MDA (oxidative stress protein) was significantly lesser and the levels of SOD and CAT (antioxidant) were higher. The levels of cortisol and AChE were significantly lesser than in the stress model group. The efficacy of CA was similar to Flx. In conclusion CA effectively prevents the changes in behaviour, neuronal ultrastructure, levels of AChE and oxidative stress biomarkers due to chronic stress in the brain and mitigates cortisol release. CA could prove an useful agent for use in the long term prevention of neurologic and behavioural changes in stress.